Production of natural food-derived vitamin c from orange juice - Mahir, Mohd Azman; Mohd Fauzi, Mohd Sufi Huzaimi; Mohamed Rehan, Aisyah (Penerbit UTHM, 2022)
Vitamin C is also called ascorbic acid and ascorbate. Usually, vitamin C can be found in citrus fruits, bell peppers, guavas, papayas, cruciferous vegetables, and tomatoes. Synthetic vitamin C supplement is also widely sold in pharmacies. Vitamin C is needed for normal growth and development of the human body, and it also functions as an antioxidant to provide plants protection from sideeffects of light during photosynthesis in plants. Shortage of vitamin C in humans may result in scurvy disease. Synthetic and food-derived vitamin C are chemically identical, however there is increasing consumer interest in natural food-derived vitamin C. This chapter provides a review of the technology used to extract vitamin C from orange juice, treatment of extracted vitamin C, quality control tests on the food-derived vitamin C, as well as the advantages of using these technologies to produce foodderived vitamin C.